Reviewing Translated Literature in the United States: A Case Study on Reviews of Translations Published by The New York Times in 2022 - Rochol, Marie (Satura, 2024)
Translations are a staple of many national literary scenes around the globe. However, while around 80 percent of all translations published between 2000 and 2009 were from an English original, only around 8 percent of them were into English (Bellos 210). When compared to the American publishing landscape, the central market in the Anglosphere, only about 3 percent of all publications are works in translation, a statistic also known as the Three Percent Problem (Sapiro 242). Many readers and researchers share “the view that reading literature from other countries is vital to maintaining a vibrant book culture and to increasing the exchange of ideas among cultures” (“About Three Percent”).